Long-term follow-up of dysphagia in adult patients with Duchenne muscular dystrophy. (September 2018) - Yamada, Yuka; Kawakami, Michiyuki; Wada, Ayako; Fukui, Shogo; Haruyama, Koshiro; Otsuka, Tomoyoshi; Liu, Meigen
Abstract: Background: Dysphagia is a well-known dysfunction in patients with Duchenne muscular dystrophy (DMD), but long-term follow-up of this symptom has not been reported. The aims of this study were to investigate swallowing status, prospectively study the prognosis of swallowing function in adult patients with DMD over the course of 6 years, and to identify clinical factors related to prognosis. Methods: Participants were 81 patients with DMD. Swallowing status was assessed using the Neuromuscular Disease Swallowing Status Scale (NdSSS) every 2 years for 6 years. Results: NdSSS was related to age, functional ability assessed using the Swinyard staging and the status of ventilator dependence. Median NdSSS changed from 6 to 4, 4 and 3 over the 4 time points. Number of patients with tube feeding increased by 5–10% every 2 years. Initial NdSSS was a predictor of future swallowing status. Conclusion: Swallowing status declined over time in patients with adult DMD, with initial NdSSS as a predictor. Highlights: Prospectively study of swallowing function over the course of 6 years in adult DMD. Ventilator dependence, Swinyard stage and age as independent predictors of NdSSS. Proportion of tube feeding increased by 5–10% every 2 years. Swallowing status declined over time, with initial NdSSS as a predictor.